Digital Mindfulness, Algorithms, and Sustainability in Shopee Loyalty: Moderated by Consumer Spirituality and Digital Intelligence - Abdul Rauf; Ismayudin Yuliyzar; Eka Hendra Priyatna; Ahmad Shabudin Ariffin; Liza Nora (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2026)
The rapid growth of e-commerce platforms has intensified competition, making customer loyalty a strategic imperative. However, existing loyalty models often overlook the interplay between digital awareness, algorithmic personalization, and value-based consumption. This study aims to examine the direct and moderating effects of digital mindfulness, recommendation algorithms, and product sustainability on customer loyalty, with consumer spirituality and digital intelligence as moderators. Using a quantitative approach, data were collected from 250 Shopee users in Tangerang Raya and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal that all three main variables significantly influence customer loyalty, with recommendation algorithms showing the strongest effect. Furthermore, consumer spirituality and digital intelligence positively moderate most relationships, although two interaction paths were statistically insignificant. The study contributes to the literature by integrating cognitive, technological, and ethical dimensions into loyalty formation. Its novelty lies in the dual moderation framework and the inclusion of spiritual and digital competencies as behavioral amplifiers. These findings offer theoretical enrichment and practical guidance for e-commerce platforms seeking to foster long-term loyalty through personalized, mindful, and value-driven strategies.